THE HANCOCK COUNTY TETRAPOD LOCALITY: A NEW MISSISSIPPIAN (CHESTERIAN) WETLANDS FAUNA FROM WESTERN KENTUCKY (USA) - Garcia W.J.; Storrs G.W.; Greb S.F. (My University, 2006)
The earliest tetrapods are known from a handful of Upper Devonian and Lower Carboniferous localities in Europe, North America, and Australia. All Upper Devonian sites and virtually all Early Carboniferous faunas are regarded as predominantly aquatic and most occur within, or are associated with, wetland habitats. A new mid- Carboniferous (Elvirian, Namurian A) fossil locality in Kentucky preserves the fi rst tetrapod fauna from the eastern portion of the Illinois Basin. Four distinct facies at the locality have yielded vertebrate material. Diverse faunas have been found in an abandoned channel/oxbow facies and a fl oodplain/lake facies. The abandoned channel/oxbow facies contains Colosteidae, Embolomeri, Rhizodontida, Dipnoi, Xenacanthiformes, Palaeonisciformes, and Gyracanthidae remains. This assemblage is similar to known Mississippian freshwater and brackishwater faunas, providing further evidence of a cosmopolitan tetrapod province during the Mississippian. A different fauna, rich in tetrapods but lacking fi sh, is associated with granular carbonate masses, rooting structures, and a paleosol in the fl oodplain/ lake facies. Isolated and associated tetrapod elements from this facies exhibit morphological adaptations that may suggest a fauna of more highly terrestrial vertebrates than previously known from the North American Mississippian. © 2006 Geological Society of America.
Keywords: ILLINOIS BASIN; MISSISSIPPIAN; TETRAPOD; WETLAND; Paleozoic::Carboniferous::Mississippian; Палеозой::Каменноугольная